Strategi Pengelolaan Tambang Galian C Di Kecamatan Padang Bolak Kabupaten Padang Lawas Utara - Widiasyih, Anugrah Sri; Harahap, Ari Ashari (Universitas Medan Area, 2025)
Mining Quarry Class C has a strategic role in regional economic development activities. Padang Bolak District has the potential for this mining as one of the largest sources of local revenue (PAD). The amount of production also always produces a lot per day. In addition to providing positive impacts, this mining also has negative impacts. So the purpose of this study is to analyze the management of Class C Mining. The data analysis used is SWOT analysis and Cartesian Diagram SWOT Analysis. The results of the study show that the management of Class C mining in Padang Bolak District, seen from the analysis of internal factors, has the strength as a large mineral and rock resource with a score of 0.756 and its main weakness is the absence of post-mining land rehabilitation activities of 0,510. Furthermore, based on the analysis of external factors, it has the opportunity as a large mineral and rock resource with a score of 0.756 and its main threat is the absence of post-mining land rehabilitation activities of 0,510. This is reinforced based on the results of the Cartesian Diagram SWOT Analysis analysis which shows that the strategy for managing Class C Quarry Mining is in quadrant I, and the strategy that must be implemented is one that focuses on growth, with strengths and many profitable opportunities.